Pengaruh Persentase Semen Opc Terhadap Kuat Tekan Mortar Geopolimer Abu Terbang Dengan Perawatan Suhu Ruang - Pratama, Rudy Satriya; Kamaldi, Alfian; Olivia, Monita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Geopolymers are environmentally friendly materials that utilize inorganic industrial waste rich in silica and alumina such as fly ash which is reacted with alkaline solutions. This study examined the effect of the percentage of Ordinary Portland Cement used as a partial substitute for fly ash against the compressive strength of mortar. The variation in the percentage of OPC used was 5%, 10%, 15%, 20% and 25%. The size of the mortar used was 50 mm × 50 mm × 50 mm. Tests on geopolymer mortar were carried out at 7, 14 and 28 days after the samples were cured under room temperature. The results showed the increase in the use of OPC would increase the compressive strength of geopolymer mortar. The use of OPC with 25% of the fly ash had a compressive strength of 11.2 MPa at 28 days after the samples were cured under room temperature. Furthermore, the compressive strength increased to 180% against the compressive strength of geopolymer mortar with the used 5% OPC. Mortar geopolymers with used of OPC 5%, 10%, 15%, and 20% had compressive strength 4 MPa, 8 MPa, 8 MPa, and 11.2 MPa after the samples were cured under room temperature. The conclusion obtained from this study was that the use of OPC of 25% as a substitute of fly ash in the geopolymer mortar was the optimum percentage which resulted in the maximum compressive strength.Keywords: Mortar, geopolymer, fly ash, compressive strength, OPC cement